Response surface methodology study on the removal of humic substances from tropical black water using sago hampas - Nurul Aida Lu, Bt Mohd Irwan Lu (Universiti Malaysia Sarawak, UNIMAS, 2012)
The study focuses on evaluation of the optimum conditions for the removal of humic substances from tropical black water using sago hampas. Response Surface Methodology (RSM) was conducted based on three-level-four-factor Box-Behnken Design in order to examine the optimum conditions for maximal adsorption of humic substances. The parameters studied were contact time (20-60 minutes), mesh size (500-900 µm), amount of dosage (100-300 mg/ml) and pH (3-7). The proportion of the total variation of the designated linear, interaction and quadratic model were 99.39 %, 99.34 % and 99.42 % respectively. The quadratic regression models were tested as the best-fit model which shows significant relationship between both the responses and the parameters. The optimum conditions based on the RSM were 40 minutes contact time with 700 µm sago hampas at 300 mg/ml and pH 3.